Neoadjuvan Chemotheraphy Responses to Local Advanced Breast Cancer Patients at Dr Moh Hoesin Hospital Palembang - Giovanno, Aldo; Mgs. Irsan Saleh; Nur Qodir; Mulawan Umar (Sriwijaya Journal of Medicine, 2020)
Neoadjuvant Chemotherapy Responses on Locally Advanced Breast Cancer Patients in General Hospital of Mohammad Hoesin Palembang. Breast cancer is a malignancy which invaded breast tissue in the form of ductal or lobular. One most therapy which given is neoadjuvant chemotherapy. Neoadjuvant Chemotherapy can reduce tumor size so that surgery can be performed with good for breast removal with Modification of Radical Mastectomy (MRM) and Breast Conservative Therapy (BCT). This purposes from this research is to find out neoadjuvant chemotherapy response in Locally Advanced Breast Cancer Patients which is received chemotherapy treatment in RSUP dr Mohammad Hoesin Palembang. This observational descriptive study was conducted at RSUP Mohammad Hoesin Palembang in period between October until November 2019. The sample of this study was locally advanced breast Cancer patients who underwent chemotherapy that met the inclusion and exclusion criteria. The data were obtained by interviews and observed medical record from the patients which were then analyzed by univariate analysis using SPSS version 25. In this study there were 34 locally advanced breast cancer patients who fulfilled the inclusion and exclusion criteria. 24 of 34 patients (70,6%) received positive response and 10 of 34 patients (29,4%) received negative response. Many factors can determine the success of chemotherapy neoadjuvant one of them is a status of molecular subtype from breast cancer patients that must be managed with hormonal therapy and the provision of appropriate chemotherapy regimens also determine the success rate of neoadjuvan therapy in local breast cancer patients.